The role of Record of Rights (Khatian) in determining title or possession: An overview - Ullah, Kalim (IIUC Studies, 2020)
Human beings are deeply related to land. Human beings take birth on land, live on land, die on land and mixes with land ultimately. As stated in the holy Quran: ‘We (Allah) created you (human beings) from the soil, we shall make you return to the soil and We shall call you back again from the soil’ (20:55). Human life is surrounded by soil i.e. land. So, land is a highly completed issue of human life involving economic, social, political, cultural and often religious systems. Land administration is thus a critical element and often a pre-condition for peaceful society and sustainable development. In administrating land, Khatian or record of rights plays a vital role to determine the rights and interests of the respective parties as supportive evidence. In this article, discussion is mainly made on the fact that Khatian or record of rights is not a document of title solely but it may be an evidence of title as well as possession. IIUC Studies Vol.15(0) December 2018: 33-46